RDWG Technique for Determination of Complex Permittivity and Moisture Content of Oil Palm Fruits - Mokhtar, Roslina; Abbas, Zulkifly; Khalid, Kaida; Hassan, Jumiah (Penerbit Universiti Sains Malaysia, 2004)
Close relationship between oil content and moisture content [Ariffin et al., 1990, Khalid & Abbas, 1992] suggests the possibility of using moisture content as a parameter to gauge fruit ripeness. It is found [Khalid & Abbas, 1992] that the amount of moisture content is higher at early stage of fruit development. Excess water is reduced in the ripe fruit as the oil accumulates in the mesocarp.